My book - Kassim, Nur Aqilah; Azero, Siti Fatimah Zahra; Abd Rashid, Siti Rasyiqah; Rosly, Nur Ezzaty; Selamat, Nordibradini (Universiti Teknologi Mara, Kedah, 2022)
“My Book” is an activity book for toddlers to pre-schoolers. An activity book is a type of book generally aimed at children, containing interactive content such as games, puzzles, quizzes, matches and other elements. Activity books may be made for entertainment, education or a mixture. This activity book includes customising and matching to the correct answer, acknowledging animal, alphabetical, body parts, numbers, colours and shapes. It provides a fun and new experience besides helping them to develop their reading ability while participating in a range of literacy and critical thinking activities.